Phosphoproteomic Analysis of Thermomorphogenic Responses in Arabidopsis - Shao, Yu-Jian; Zhu, Qiao-Yun; Yao, Zi-Wei; Liu, Jian-Xiang (Frontiers in Plant Science, 2021)
Plants rapidly adapt to elevated ambient temperature by adjusting their growth and developmental programmes. To date, a number of experiments have been carried out to understand how plants sense and respond to warm temperatures. However, how warm temperature signals are relayed from thermosensors to transcriptional regulators is largely unknown. To identify new early regulators of plant thermo-responsiveness, we performed phosphoproteomic analysis using TMT (Tandem Mass Tags) labeling and phosphopeptide enrichment with Arabidopsis etiolated seedlings treated with or without 3 hours of warm temperatures (29°C). In total, we identified 13,160 phosphopeptides in 5,125 proteins with 10,700 quantifiable phosphorylation sites. Among them, 200 sites (180 proteins) were up-regulated while 120 sites (87 proteins) were down-regulated by elevated temperature. GO (Gene Ontology) analysis indicated that phosphorelay-related molecular function was enriched among the differentially phosphorylated proteins. We selected ATL6 (ARABIDOPSIS TOXICOS EN LEVADURA 6) from them and expressed its native and phosphorylation-site mutated (S343A S357A) forms in Arabidopsis, and found that the mutated form of ATL6 was less stable than that of the native form both in vivo and in cell-free degradation assays. Taken together, our data revealed extensive protein phosphorylation during thermo-responsiveness, providing new candidate proteins/genes for studying plant thermomorphogenesis in future.